Effect of annealing on the microstructures and deformation behaviour of Ti-50.7at.%Ni shape memory alloy - Hastuti, Kurnia (SAGE Publications Ltd., 2016)
In this paper Ti-50.7at.%Ni as a commercial material was examined to analyse the effect of annealing temperature on the microstructure and deformation behaviour. It was found that the microstructure and deformation behaviour of as-received material was affected by the existence of dislocations that was introduced during manufacturing process. The presence of martensite variant and the B2 austenite broadening in XRD spectra of as-received material verified this conclusion. However, annealing treatment has gradually eliminated this effect. The plateau region on stress-strain curve which was absent in the as-received material started to appear and get longer with increasing annealing temperature. Maximum tensile strength was observed in the sample annealed at 400? for 1h. Annealing treatment above 500? transformed the B19 martensite to B2 austenite, which leads to a decrease in the tensile strength of the material. Nearly perfect superelasticity was found in the as-received material and sample annealed at 300?.